A perspectiva assimétrica sobre punição segundo William K. Estes e Murray Sidman: uma análise conceitual - Almeida, Deborah Paz de (2017)
On Behavior Analysis it is possible to understand punishment based mainly on two perspectives: asymmetrical, that defines punishment by it‘s procedures; And symmetrical, which also refers to the behavioral process. The main authors of these perspectives are Skinner, and Azrin and Holz, respectively. Each of these perspectives results on different experimental and practical implications. The objective of the present work is to analyze the development of the concepts of punishment by William K. Estes and Murray Sidman, two authors who are prominent on the asymmetrical perspective, but have been less studied than Skinner. For this purpose, texts about punishment, experimental and theoretical-conceptual, written by both authors, were selected from the PsycNet platform, from a list of Murray Sidman articles available at the Experimental Psychology Laboratory of PUC-SP, and by contact with other researchers. A total of four texts written by Estes and 16 texts written by Sidman were found, in addition to an interview given by Sidman to Per Holth. The texts were then fully read, with the excerpts that made reference to: a) definitions of punishment, aversive or punishing stimulus, coercion or aversive control; b) effects of punishment; c) explanation of its effects; d) debates with other authors about the subject; and e) discussion about the use of punishment; being highlighted and analyzed. Based on this analysis it was possible to identify similarities between the concepts proposed by Estes, Sidman and Skinner. In relation to definition, the similarities between Sidman and Skinners proposals, and the characterization of punishment proposed by Estes, stand out. By describing possible weakening effects of punishment, Estes and Sidman point out to its temporality and to the aversive relations that emerge by stimulus conditioning. On the subject of the explanation given to punishment effects, Skinner, Estes and Sidman all point out to the possibility of strengthening of a response capable of reducing the aversive stimulation that the punished response itself generates, and Estes later presents some criticism to this interpretation; and Sidman emphasizes the competition of reinforcing and punishing consequences as another possible interpretation that explains the observed effects. Estes and Sidman don‘t dialog among themselves, even though both present debates with Skinner. Lastly, Estes and Sidman dedicate some part of their work to discuss the implication of the practical uses of punishment